How biased is the behavior of the individual investor in warrants? - Abreu, Margarida (2017)
Based on the actual trading behavior of individual investors in the Portuguese financial market during almost ten years this paper examines the socio‐demographic characteristics of retail investors in warrants, and discusses the hypothesis that some behavioral biases do have an impact on the investors’ predisposition to invest and trade in warrants, a complex financial instrument. One finds that there is a profile of investors in warrants: younger and less educated men are more likely to invest in warrants and that overconfident, disposition‐prone and investors exhibiting a gambling attitude are more likely to invest and trade in warrants. Secondly, the gambling motive seems to be a distinguishing characteristic of investors in warrants. In other words, when investors are driven to trade in financial markets for pleasure/fun they tend to trade complex products more and to trade simple and easier to understand financial instruments less. Finally, the higher the intensity of trading the more relevant are the disposition and the gambler’s biases.